2004
DOI: 10.1124/jpet.104.075283
|View full text |Cite
|
Sign up to set email alerts
|

Sulodexide Attenuates Myocardial Ischemia/Reperfusion Injury and the Deposition of C-Reactive Protein in Areas of Infarction without Affecting Hemostasis

Abstract: Several glycosaminoglycans (GAGs) have been demonstrated to protect the ischemic heart against reperfusion injury, in part, by modulating activation of the complement cascade. The present study assessed the cardioprotective effects of sulodexide (KRX-101), a mixture of GAGs composed of 80% lowmolecular mass heparin and 20% dermatan sulfate. KRX-101 differs from other GAGs (e.g., heparin) in that it has limited anticoagulant efficacy and can be administered orally. The experimental protocol was designed to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 27 publications
3
36
1
1
Order By: Relevance
“…Although these results did not achieve statistical significance, clear evidence of a downward trend in this serum marker of irreversible myocardial tissue injury was obtained. The reduced statistical power observed in this study versus previous results obtained in our laboratory for this marker (Lauver et al, 2005) may have resulted from the curtailed period of reperfusion in the current study. There may have been insufficient time for cTnI to reach peak plasma concentrations in this study.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Although these results did not achieve statistical significance, clear evidence of a downward trend in this serum marker of irreversible myocardial tissue injury was obtained. The reduced statistical power observed in this study versus previous results obtained in our laboratory for this marker (Lauver et al, 2005) may have resulted from the curtailed period of reperfusion in the current study. There may have been insufficient time for cTnI to reach peak plasma concentrations in this study.…”
Section: Discussioncontrasting
confidence: 56%
“…The immunofluorescent method for detection of CRP was based on protocols previously developed in our laboratory (Lauver et al, 2005). Briefly, tissue samples used for infarct size determination were fixed in 10% buffered formalin immediately after the completion of the experimental protocol.…”
mentioning
confidence: 99%
“…In addition, selective GAGs are known to possess anti-complement activity in addition to their classical roles as anticoagulants. Recently we reported that sulodexide effectively reduced myocardial infarct size after ischemia and reperfusion in the rabbit heart when administered periodically throughout the four hour reperfusion period (48) (Fig. 1).…”
Section: Prevention Of Reperfusion Injurymentioning
confidence: 89%
“…Deposition of a sufficient number of the lytic membrane attack complexes on a nucleated target cell results in disruption of the cell membrane and ultimately cell lysis. Intravenous administration of 0.5 mg/kg sulodexide, commencing immediately upon reperfusion and at hourly intervals during reperfusion was associated with a significant decrease in myo-D. A. LAUVER AND B. R. LUCCHESI cardial infarct size expressed as a percentage of the area at risk when compared with vehicle-treated control rabbits (48).…”
Section: Prevention Of Reperfusion Injurymentioning
confidence: 93%
“…We have used an in vivo biomarker of MI used clinically that has been shown to correlate temporally with the degree of myocardial cell death (30). Troponin release measured in the serum 24 h post-MI by ELISA was shown to be no different between groups, suggesting similar infarct size and therefore likely not accounting for the increased labeled PMN migration in the HSϩMI group.…”
Section: Discussionmentioning
confidence: 99%